Red Pasta: What is the Technological Impact of The Enrichment of Beet Ingredient in Fresh Pasta? - Filho, Josemar Gonçalves De Oliveira [UNESP]; Lemes, Ailton Cesar; Filho, Ricardo Pereira Cruz; Guimarães, Rafaiane Macedo; Oliveira, Kamylla Lina; Santana, Gabriela Silva; Danesi, Eliane Dalva Godoy; Egea, Mariana Buranelo (Codon Publications, 2021)
The objective of this study was to evaluate the partial replacement of wheat flour by beet flour (BF) in fresh pasta production, analyzing its chemical, technological, and sensorial characteristics. BF showed good water (4.2 g water/g flour) and oil absorption (2.2 g oil/g flour), water solubility (67.3%), and emulsifying properties (30.0%). The incorporation of BF in fresh pasta formulations improved the nutritional value of the pasta, increased the ash (1.65 to 2.16 g/100g) and fiber contents (1.31 to 12.29 g/100g) of the fresh pasta, and decreased the lipid contents (50.0% reduction), thereby causing changes in its cooking properties. The antioxidant capacity (0.5 to 4.76%) and the content of total phenolics (69.1 to 70.5 mg/100g) and betalains (0.04 to 0.16 mg/100g) also increased with the addition of BF, improving the functional profile of the pasta. In the sensory profile, the pasta formulated with the highest concentrations of BF demonstrated the highest intensities for the sensory attributes among fresh pasta evaluated. In general, it was shown that BF represents a promising ingredient to produce new fresh pasta with functional characteristics.
Keywords: antioxidant activity; betalains; functional product